CLINICAL CHARACTERISTICS OF PEDIATRIC MORTALITY IN THE MEDICAL INTENSIVE CARE UNIT, VIETNAM NATIONAL CHILDREN’S HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: Understanding the characteristics of pediatric patients who died in the Pediatric Intensive Care Unit (PICU) is essential for developing interventions to reduce mortality risk. Methods: A prospective descriptive study was conducted on children aged 1 month to 16 years who died in the PICU. Collected variables included age, gender, source of admission, clinical and laboratory findings, therapeutic interventions before and during PICU stay, and the number of deaths. Data were analyzed according to the study objectives. Categorical variables were expressed as percentages, while continuous variables were expressed as means and standard deviations. Categorical variables were analyzed using the Chi-square (χ²) test or Fisher’s exact test as appropriate. Univariate and multivariate logistic regression analyses were performed to determine the odds ratios (ORs) with 95% confidence intervals (CIs). A two-tailed test was applied, and a p-value of
Keywords: Mortality, children, PICU, diseases